ANALISIS FAKTOR-FAKTOR RENDAHNYA KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DITINJAU DARI MOTIVASI BELAJAR SISWA DI KELAS VII SMP NEGERI 5 PADANGSIDIMPUAN - Agnes M Siregar; Roslian Lubis; Nunik Ardiana (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2023)
Problem solving ability is the most basic ability in mathematics that teacher must train students. Different learning motivation among student can affect students’ ability to solve problems. This study aims to desribe students’ problem solving abilities according to the levels of learning motivation (1) High, (2) Medium (3) Low. The subjects in this study were 24 students of seventh grade students of SMP Negeri 5 Padangsidimpuan. The method uses descriptive qualitative. Data collection techniques use questionnaires, tests, and interviews. The results shows that haigh learning motivation students have problem-solving skills that tended to be good, students are able to fulfill the four problem-solving indicators according to Polya, namely (1) understanding the problem, (2) making plans, (3) carryng out plans, (4) checking back. Medium learning motivation students have medium problem-solving abilities students are able to fulfill two or three indicators, (1) understanding the problem, (2) making plans, (3) some students have problems implementing plans for completion but some of them are able to carry out plans. Low learning motivation students are able to fulfill two indicators, (1) understanding the problem, (2) unable to determine which settlement plan to choose.